Efficient Keyword Extraction and Text Summarization for Reading Articles on Smart Phone - Jeong, Hyoungil; Ko, Youngjoong; Seo, Jungyun (Computing and Informatics, 2016)
These days, we can connect to the internet from almost anywhere, allowing us to access web content, including newspapers, magazines, blogs and websites, using mobile devices such as a smart phone. However, people sometimes struggle to read and use the contents due to the nature of these devices such as a small display, low display resolution and limited computing resources (low CPU speed and little memory). This paper aims to develop a convenient interface that provides keyword extraction, summary generation and search engine to users. We apply the proposed summarization method to Korean and English news articles and evaluate it using several experiments on single and multiple news article test collections and user-receptiveness tests. Since the proposed method shows a good performance on these experiments and tests, we think that this interface can help users more efficiently to read the news articles on various mobile devices.